Rekayasa Artificial Intelegent (AI) bagi Guru untuk Menunjang Literasi Digital pada Pembelajaran - Ryzal Perdana; Apri Wahyudi; Gde Satya Yudha Tama; Ade Bagus Putri (LPPM Politeknik Piksi Ganesha, 2025)
The use of Artificial Intelligence (AI) for teachers to support digital literacy in learning is an increasingly relevant issue in the context of modern education. This community service project outlines the main issue by explaining the challenges and potential of AI in learning and helping teachers improve their individual professionalism. The community service method used was a literature review, which included an analysis of various sources and views related to the use of AI in secondary education. This was conducted by going directly to the field to find out the extent of the problem. The results showed that many teachers still do not understand the use of Artificial Intelligence (AI) as a practical tool that makes things easier within their limited capabilities. It was found that some teachers already understand how technology can speed up work and simplify administrative work, but others still need to improve their skills. In conclusion, teachers' understanding of the role of AI in the digital transformation of education is still at an early stage, technical and pragmatic.